The history of agricultural machinery repair system in Russia - V. I. Chernoivanov (Сельскохозяйственные машины и технологии)
The paper highlights the imperative for the maintenance and repair of agricultural machinery. (Research purpose) The research aims to undertake a retrospective analysis illuminating the evolution and establishment of the machine repair system. This analysis spans from the production of the inaugural Soviet tractor to the advancement and production of contemporary machinery and equipment. (Materials and methods) The paper analyses publications from diﬀerent periods focused on the challenges surrounding the establishment of a centralized system for the repair and maintenance of machinery and equipment across all stages of agricultural production development. (Results and discussion). The paper sheds the light on the dynamics of tractor production in the early 1930s, detailing the transition from reliance on imports to the utilization of domestic agricultural machinery in the local market, alongside the phases involved in establishing a domestic repair service system. Furthermore, it explores the evolution of repair workshops at machinery technological stations from 1928 to 1957 and outlines the structuring of a repair depot within the enterprises of the All-Union Association «Soyuzselkhoztekhnika» between 1961 and 1990. Additionally, the paper delves into the analysis of repair strategies, ranging from individualized to in-line approaches. The paper underscores the pivotal role of academic and industrial science in equipping repair enterprises with essential technological documentation, repair equipment, and supplementary materials. It also highlights their contribution to the development of methodological support for maintenance and repair operations at the level of a centralized system. (Conclusions) The paper presents information on the research and design activities undertaken by specialized laboratories and departments within the All-Union Scientific Research Institute of Agricultural Mechanization VIM from 1930 to 1961. It acknowledges the significant contributions of scientists and experts in the domains of machine wear theory and the standardization of repair technologies. Furthermore, the paper emphasizes the critical influence of the State Union Scientific Research Technological Institute for the Repair and Operation of Tractors and Agricultural Machines GOSNITI between 1963 and 2013 on establishing a robust machinery repair and maintenance system. It outlines the potential and future directions for the evolution of a service system for agricultural machinery.